2016
DOI: 10.4172/2161-0983.1000179
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Insect Assemblage and Functional Groups along a Grazing Gradient in an Arid Environment

Abstract: Exotic livestock may affect plant and pollinator composition as well as their interactions. Changes in pollinator assemblage (e.g. composition) may alter pollination process and, therefore, plant reproduction. This study examined seven independent paddocks environmentally similar but with increasing livestock densities, in Patagonian Monte Desert. This allows investigating the response of different insect groups to livestock effect on vegetation along a grazing gradient. Water traps was used to capture insects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Particularly, pollinators, solitary bees and herbivores showed a positive association with flowering plant density while dipteran pests and predator did not. This is in accordance with a previous work in the same study area, showing that the composition of the pollinator assemblage was highly associated with the abundance of the plant species they visited (Tadey, 2016). At higher trophic levels, it was observed that predator abundance increased while the proportion of dipteran pests and the abundance of herbivores and pollinators decreased.…”
Section: Discussionsupporting
confidence: 93%
“…Particularly, pollinators, solitary bees and herbivores showed a positive association with flowering plant density while dipteran pests and predator did not. This is in accordance with a previous work in the same study area, showing that the composition of the pollinator assemblage was highly associated with the abundance of the plant species they visited (Tadey, 2016). At higher trophic levels, it was observed that predator abundance increased while the proportion of dipteran pests and the abundance of herbivores and pollinators decreased.…”
Section: Discussionsupporting
confidence: 93%
“…A linear regression approach was taken, as used previously (Tadey 2016). Linear regression was used to relate percentage cover of Smooth Brome to Hemiptera abundance, biomass, species richness, and species diversity.…”
Section: Methodsmentioning
confidence: 99%